2000
DOI: 10.1104/pp.124.1.313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein and Transcript Levels of the Chaperonin Containing Tailless Complex Protein-1 and Tubulin during Light-Regulated Growth of Oat Seedlings

Abstract: In grass seedlings the network of cortical microtubules is reorganized during light-dependent growth of coleoptiles and mesocotyls. We investigated the effects of light-dependent growth on the relative steady-state levels of the mRNAs and protein levels of ␣-tubulin and the ⑀-subunit of the chaperonin containing tailless complex protein-1 in oat (Avena sativa) coleoptiles, which were grown in different light conditions to establish different growth responses. The soluble pools of the ⑀-subunit of the chaperoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We observed five‐fold higher abundances of tubulin in HL, which may be a result of an increased demand for intracellular transport to achieve higher biosynthetic rates. Interestingly, TCP‐1 chaperones, which were also up‐regulated in HL E. huxleyi , act on a number of proteins, but are particularly known for their role in the biogenesis and arrangement of tubulin (Moser et al ., ; Brackley & Grantham, ). We also observed two‐fold higher abundances of cell division cycle proteins in HL, which may be necessary to support the three‐fold higher growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…We observed five‐fold higher abundances of tubulin in HL, which may be a result of an increased demand for intracellular transport to achieve higher biosynthetic rates. Interestingly, TCP‐1 chaperones, which were also up‐regulated in HL E. huxleyi , act on a number of proteins, but are particularly known for their role in the biogenesis and arrangement of tubulin (Moser et al ., ; Brackley & Grantham, ). We also observed two‐fold higher abundances of cell division cycle proteins in HL, which may be necessary to support the three‐fold higher growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the extensive characterization of CCT’s structure and functions in other eukaryotes, information on plant CCT and its de novo substrates is scarce, partly due to the difficulty in obtaining loss-of-function mutants since CCT’s functions are essential for cell survival. Earlier studies in maize and oats using anti-CCT antibodies showed co-sedimentation of tubulin and CCT subunits in sucrose fractionation and co-immunoprecipitation of CCTε (CCT5) with β-tubulin (Himmelspach et al , 1997; Moser et al , 2000). More recently, Xu et al (2011), after analysing weak cct8 mutant alleles, reported that CCT is essential for cell-to-cell trafficking and stem cell function of the KNOTTED1 homeobox family of transcript factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp70 is an anti-apoptotic chaperone protein [50] that inhibits mitochondrial release of cytochrome c and blocks procaspase-9 recruitment to the apoptosome complex [51].…”
Section: Discussionmentioning
confidence: 99%